Fermented Biomass of Arthrospira platensis as a Potential Food Ingredient - Polona Jamnik; Nik Mahnič; Aleksandra Mrak; Lea Pogačnik; Barbara Jeršek; Alberto Niccolai; Jasmina Masten Rutar; Nives Ogrinc; Larisa Dušak; Blaž Ferjančič; Mojca Korošec; Ana Cerar; et al. (MDPI AG, 2022)
Lactic acid fermentation (LAF) is known to improve nutritional properties and functionality and to extend the shelf life of foods. We studied the LAF of Arthrospira platensis as the sole substrate using Lactobacillus plantarum as the starter culture. Fermented (FB) and non-fermented broth (NFB) were analysed by means of pH, lactic acid bacteria (LAB) count, lactic acid concentration, microbiological safety, and nutritional composition. Additionally, water and ethanol extracts were prepared on which total phenolic content, DPPH radical scavenging activity, and cellular antioxidant activity were determined. The maximum increase in LAB count and lactic acid concentration and drop in pH was observed in the first 24 h of fermentation. Total phenolic content and DPPH radical scavinging activity of ethanol extracts increased after fermentation compared with NFB. Ethanol extracts of FB have been shown as a potential source of antioxidants, which efficiently lowered oxidation level in the cells of yeast Saccharomyces cerevisiae, as well as the oxidative damage of lipids. Additionally, the level of non-protein nitrogen increased, indicating higher protein bioavailability, and fat content decreased in comparison with NFB. No presence of pathogenic bacteria and low pH indicate enhancement of FB microbiological stability. Therefore, inclusion of fermented A. platensis into food products could lead to added-value foods based on microalgae.